Systematic evaluation of SARS‐CoV‐2 antigens enables a highly specific and sensitive multiplex serological COVID‐19 assay. Issue 7 (19th July 2021) - Hober, Sophia; Hellström, Cecilia; Olofsson, Jennie; Andersson, Eni; Bergström, Sofia; Jernbom Falk, August; Bayati, Shaghayegh; Mravinacova, Sara; Sjöberg, Ronald; Yousef, Jamil; Skoglund, Lovisa; Kanje, Sara; et al.
Abstract: Objective: The COVID‐19 pandemic poses an immense need for accurate, sensitive and high‐throughput clinical tests, and serological assays are needed for both overarching epidemiological studies and evaluating vaccines. Here, we present the development and validation of a high‐throughput multiplex bead‐based serological assay. Methods: More than 100 representations of SARS‐CoV‐2 proteins were included for initial evaluation, including antigens produced in bacterial and mammalian hosts as well as synthetic peptides. The five best‐performing antigens, three representing the spike glycoprotein and two representing the nucleocapsid protein, were further evaluated for detection of IgG antibodies in samples from 331 COVID‐19 patients and convalescents, and in 2090 negative controls sampled before 2020. Results: Three antigens were finally selected, represented by a soluble trimeric form and the S1‐domain of the spike glycoprotein as well as by the C‐terminal domain of the nucleocapsid. The sensitivity for these three antigens individually was found to be 99.7%, 99.1% and 99.7%, and the specificity was found to be 98.1%, 98.7% and 95.7%. The best assay performance was although achieved when utilising two antigens in combination, enabling a sensitivity of up to 99.7% combined with a specificity of 100%. Requiring any two of the three antigens resulted in a sensitivity of 99.7% and a specificity of 99.4%. Conclusion: These observations demonstrate that a serological test based on a combination of several SARS‐CoV‐2 antigens enables a highly specific and sensitive multiplex serological COVID‐19 assay. Abstract : Five selected antigens show different patterns when used for detection of IgG antibodies in samples from 331 COVID‐19 patients and convalescents, and 2090 negative controls. Analysing multiple antigens simultaneously can generate data that can be used for diagnostic purposes as well as to further understand the responses of the immune system. The multifaceted data that our method delivers furthermore allow for an adaptation of the outcome to the individual analysis, giving as accurate answers as possible regardless of time passed since infection onset.